Gambaran Tingkat Nyeri Haid (Dysminorhea) pada Remaja Putri di Kelurahan Gedanganak - Isabel Maria Marques; Suwanti Suwanti (Universitas Ngudi Waluyo, 2022)
Dysmenorhea is pain felt in the lower abdomen during menstruation caused by uterine muscle spasms. This pain can be felt before and after menstruation which is colicky or continuous. Dysmonorhea often occurs in adolescents. To find out the description of the level of menstrual pain (dysminorhea) in young women in Gedanganak Village. This research is a descriptive research. The population is 1000 young women in the Gedanganak Village and a sample of 91 people with purposive sampling and using the NRS questionnaire with inclusion criteria. Data analysis with frequency distribution. The study showed an overview of the level of menstrual pain in young women in the Gedanganak Village, mostly in the moderate pain category, namely 43 respondents (43%), 7 respondents in the non-pain category (7%), 20 respondents in the mild pain category (20%), and 21 in severe pain. respondents (21%). It is hoped that young women can increase their knowledge and information about handling dysmenorrhea such as reading books, asking health workers or using facilities such as the internet.AbstrakDysmenorhea merupakan nyeri yang dirasakan pada perut bagian bawah selama masa menstruasi yang disebabkan oleh kejang otot uterus. Nyeri ini dapat dirasakan sebelum dan sesudah menstruasi yang bersifat kolik atau terus menerus. Dysmonorhea banyak terjadi pada remaja. Untuk mengetahui gambaran tingkat nyeri haid (dysminorhea) pada remaja putri di Kelurahan Gedanganak. Penelitian ini berupa penelitian deskriptif. Populasinya adalah remaja putri di Kelurahan Gedanganak sebanyak 1000 orang dan sampel sebanyak 91 orang dengan purposive sampling dan menggunakan kuesioner NRS dengan kriteria inklusi. Analisa data dengan distribusi frekuensi. Penelitian menunjukkan gambaran tingkat nyeri haid pada remaja putri di Kelurahan Gedanganak sebagian besar kategori nyeri sedang yaitu sebanyak 43 responden (43%), kategori tidak nyeri 7 responden (7%), kategori nyeri ringan 20 responden (20%), dan nyeri berat 21 responden (21%). Diharapkan untuk remaja putri dapat meningkatkan pengetahuan dan informasi tentang penanganan dysminorhea seperti membaca buku, bertanya kepada petugas kesehatan atau menggunakan fasilitas seperti internet.